Microbial Diversity and Mineralogical-Mechanical Properties of Calcitic Cave Speleothems in Natural and in Vitro Biomineralization Conditions - Dhami, Navdeep K.; Mukherjee, Abhijit; Watkin, Elizabeth L. J. (Frontiers in Microbiology, 2018)
Natural mineral formations are a window into important processes leading to carbon storage and mineralized carbonate structures formed through abiotic and biotic processes. In the current study, we made an attempt to undertake a comprehensive approach to characterize the mineralogical, mechanical, and microbial properties of different kinds of speleothems from karstic caves; with an aim to understand the bio-geo-chemical processes in speleothem structures and their impact on nanomechanical properties. We also investigated the biomineralization abilities of speleothem surface associated microbial communities in vitro. Mineralogical profiling using techniques such as X-ray powder Diffraction (XRD) and Tescan Integrated Mineral Analyzer (TIMA) demonstrated that calcite was the dominant mineral in the majority of speleothems with Energy Dispersive X-ray Analysis (EDS) indicating a few variations in the elemental components. Differing proportions of polymorphs of calcium carbonate such as aragonite and vaterite were also recorded. Significant variations in trace metal content were recorded through Inductively Coupled Plasma Mass Spectrometer (ICP-MS). Scanning Electron Microscopy (SEM) analysis revealed differences in morphological features of the crystals which varied from triangular prismatic shapes to etched spiky forms. Microbial imprints and associations were seen in a few sections. Analysis of the associated microbial diversity showed significant differences between various speleothems at Phylum level; although Proteobacteria and Actinobacteria were found to be the predominant groups. Genus level microbial associations showed a relationship with the geochemistry, mineralogical composition, and metal content of the speleothems. The assessment of nanomechanical properties measured by Nanoindentation revealed that the speleothems with a dominance of calcite were stronger than the speleothems with mixed calcium carbonate polymorphs and silica content. The in vitro metabolic activity of the microbial communities associated with the surfaces of the speleothems resulted in calcium carbonate crystal precipitation. Firmicutes and Proteobacteria dominated these populations, in contrast to the populations seen in natural systems. The precipitation of calcium carbonate crystals in vitro indicated that microbial metabolic activity may also play an important role in the synthesis and dissociation of biominerals in the natural environment. Our study provides novel evidence of the close relationship between mineralogy, microbial ecology, geochemistry, and nanomechanical properties of natural formations.